Teachers’ Demographic Factors and Retention in Public Senior Secondary Schools in Rivers State Nigeria - Osuji; Catherine U. (INTERNATIONAL JOURNAL OF SOCIAL SCIENCES AND MANAGEMENT RESEARCH, 2026)
The study investigated the relationship between teachers’ demographic factors and retention in public secondary schools in Rivers State. Three objectives and three research questions guided the study. The study adopted a correlational design. The population of the study consist of 6,174 teachers comprising of 3072 male teachers and 3102 female teachers in the 311 public senior secondary schools in Rivers State. The sample for this study was 741 respondents; comprising 311 male teachers’ and 430 female teachers. The instruments used for data collection of data for this study were designed by the researcher titled ‘Teachers’ Demographic Factors Questionnaire” (TDFQ) and retention Questionnaire (TRQ). The completed copies of the questionnaire were analyzed for reliability using Cronbach Alpha method. The reason was to establish the internal consistency of the instrument. The test yielded reliability coefficients of 0.86, 0.85 and 0.83 with the average reliability coefficient of 0.85 which showed the instruments were reliable. Pearson Product Moment Correlation Statistics was used to answer the research questions while linear regression analysis was used to test the hypotheses at an alpha level of 0.05. The study concluded that there are significant perceptions into factors affecting teachers’ retention in public secondary schools in Rivers State. The findings highlight a strong positive influence of academic qualifications, age and gender on teachers' retention. The findings from the study revealed that there is a very strong positive relationship between academic qualifications and teachers' retention in public secondary schools in Rivers State. The study recommends, among others, that State Government should increase funding for advanced educational opportunities and qualifications for teachers to cater to the needs of teachers at various stages of their careers.